The Efficacy of Acupuncture in Chemotherapy-Induced Peripheral Neuropathy: Systematic Review and Meta-Analysis - Chien, Tsai-Ju; Liu, Chia-Yu; Fang, Ching-Ju; Kuo, Chun-Yu (Integrative cancer therapies, 2019)
Background: Chemotherapy-induced peripheral neuropathy (CIPN) has no cure, but acupuncture may provide relief through its known neuromodulation or neuroendocrine adjustment. This review aimed to assess the efficacy of acupuncture in treating CIPN. Method: A literature review following the PRISMA Statement was performed, searching 7 databases from inception through August 2019. All studies were clinical trials of the effect of acupuncture on CIPN. The methodological quality of these trials was assessed using Cochrane criteria; meta-analysis software (RevMan 5.2) was used to analyze the data. Data Sources: The databases searched were the following: MEDLINE (Ovid), Embase, Cochrane CENTRAL, Scopus, World Health Organization International Clinical Trials Registry Platform, CNKI (China National Knowledge Infrastructure), and Wanfang Med Online. Results: We examined 386 cancer patients from 6 randomized control trials, which had high quality, based on the modified Jadad scale. Meta-analysis showed that acupuncture led to significant improvements in pain scores (−1.21, 95% confidence interval [CI] = −1.61 to −0.82, P < .00001) and nervous system symptoms based on Functional Assessment of Cancer Therapy/Neurotoxicity questionnaire scores (−2.02, 95% CI = −2.21 to −1.84, P < .00001). No significant change was noted in nerve conduction velocity (1.58, 95% CI = −2.67 to 5.83, P = .47). Conclusion: Acupuncture can effectively relieve CIPN pain and functional limitation. The limited number of subjects warrants a larger scale study.